2017
DOI: 10.1289/ehp1062
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to Perfluoroalkyl Substances and Metabolic Outcomes in Pregnant Women: Evidence from the Spanish INMA Birth Cohorts

Abstract: Background:Exposure to perfluoroalkyl substances (PFASs) may increase risk for metabolic diseases; however, epidemiologic evidence is lacking at the present time. Pregnancy is a period of enhanced tissue plasticity for the fetus and the mother and may be a critical window of PFAS exposure susceptibility.Objective:We evaluated the associations between PFAS exposures and metabolic outcomes in pregnant women.Methods:We analyzed 1,240 pregnant women from the Spanish INMA [Environment and Childhood Project (INfanci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
54
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 121 publications
(60 citation statements)
references
References 42 publications
5
54
1
Order By: Relevance
“…2016 ). Development of gestational diabetes was associated with the serum PFOA concentrations in pregnant women, although another study showed less clear associations ( Matilla-Santander et al. 2017 ; Valvi et al.…”
Section: Discussionmentioning
confidence: 99%
“…2016 ). Development of gestational diabetes was associated with the serum PFOA concentrations in pregnant women, although another study showed less clear associations ( Matilla-Santander et al. 2017 ; Valvi et al.…”
Section: Discussionmentioning
confidence: 99%
“…Sex-specific associations between PFASs and fetal growth as well as modifying effects of PFASs on health by parity and maternal metabolic diseases have previously been suggested [ 17 , 29 ]. Tests for heterogeneity were performed by examining p -values for interaction term between each of the exposure and the potential modifier [ 30 , 31 ]. Moreover, we also conducted analyses separately for each study sample to examine the consistency of the results across strata.…”
Section: Methodsmentioning
confidence: 99%
“…21 Clearly, the effect of PFAS exposure on the health of both mother and baby is of concern. Several studies have reported links between PFAA exposure and perturbation in lipid metabolism [22][23][24] and glucose tolerance 24 during pregnancy. Exposure to some PFAAs during early life stages has also been linked to adverse health effects such as reduced birth weight and immune toxicity.…”
Section: 20mentioning
confidence: 99%